Analisis Pendahuluan Pengembangan Modul Fiksi Realistik dalam Pembelajaran Apresiasi Sastra di Sekolah Dasar - Serani, Gabriel; Oktaviani, Ursula Dwi; Kurniati, Agusta; Parida, Lusila (Universitas Muhammadiyah Surabaya, 2025)
This study investigates the implementation of realistic fiction instruction in fourth-grade classrooms, identifying the challenges in achieving optimal learning outcomes and addressing the need for a more effective approach. A descriptive qualitative approach was used, including document analysis, surveys, classroom observations, and interviews. The findings reveal that current teaching methods are insufficient in fostering deep literary appreciation among students. To address these issues, a learning module integrated with QR Codes is developed. The module incorporates digital content, fostering engagement and supporting a more interactive, multimodal approach to literature appreciation, ultimately promoting cognitive, affective, and psychomotor growth in students.